Nghiên cứu tổng hợp vật liệu Ti-SBA-15 từ thủy tinh lỏng Việt Nam và tính chất xúc tác trong phản ứng oxi hóa alpha-pinen - Tuyến, Nguyễn Đình; Hoài Nam, Lê Thị (Vietnam Journal of Chemistry, 2014)
A new method to prepare mesoporous material Ti-SBA-15, which was expected to be a commercial synthesis was presented. The obtained Ti-SBA-15 with hexagonal structure were successfully prepared by using sodium silicate and nontoxic precursors, which are low cost and available in Vietnam. These materials were characterized by different techniques such as XRD, IR, BET, SEM, HRTEM, UV-VIS. It shown that Ti-SBA-15 have very uniform pore size (3.5- 9.5 nm). These catalysts were tested in the oxidation reaction α-pinene with hydrogen peroxide as oxidation agent. The results shown that Ti-SBA-15 had activity and stability higher than Ti-MCM-41 under lower reaction temperature than other oxide catalysts. This commercial preparation method is a great potential background to scale-up and apply mesoporous material Ti-SBA-15 in fine chemistry and pharmaceutical chemistry.